2021
DOI: 10.2196/26349
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality for Sedation During Atrial Fibrillation Ablation in Clinical Practice: Observational Study

Abstract: Background Connected devices are dramatically changing many aspects in health care. One such device, the virtual reality (VR) headset, has recently been shown to improve analgesia in a small sample of patients undergoing transcatheter aortic valve implantation. Objective We aimed to investigate the feasibility and effectiveness of VR in patients undergoing atrial fibrillation (AF) ablation under conscious sedation. Meth… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 28 publications
0
6
2
Order By: Relevance
“…However, the level of pain reported was low in both groups, as were the doses of medications. The VAS pain perception scores are in contradiction with those of Roxburgh et al, who found a significant difference between groups [9]: indeed, our absolute result for VAS score in the VRH group is quite close to Roxburgh et al's (3.74 in our study and 3.5 in their study, respectively), but the results in the two control groups are different (3.07 vs. 4.3, respectively).…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…However, the level of pain reported was low in both groups, as were the doses of medications. The VAS pain perception scores are in contradiction with those of Roxburgh et al, who found a significant difference between groups [9]: indeed, our absolute result for VAS score in the VRH group is quite close to Roxburgh et al's (3.74 in our study and 3.5 in their study, respectively), but the results in the two control groups are different (3.07 vs. 4.3, respectively).…”
Section: Discussioncontrasting
confidence: 98%
“…Roxburgh et al recently published a similar study in a population undergoing the AF cryoablation [9], but our results are opposite of theirs, particularly in terms of procedural comfort. Their study recruited 48 patients, the duration of procedures was not reported, and the main endpoint was assessed 45 min after the end of the procedure in patients receiving narcotics, which could be a bias (for example memory bias).…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…A recent pilot study of virtual reality glasses in colonoscopy patients [36] revealed that the virtual reality experience provided a pleasant distraction and did not compromise the procedure. A prospective cohort study in patients presenting for ablation for atrial fibrillation in the cardiology suite compared a virtual reality headset with a historical control [37 ▪ ]. Patients in the virtual reality group reported less pain and felt more comfortable.…”
Section: Devicesmentioning
confidence: 99%
“…34,63 Virtual reality can enable existing treatments to be offered at scale through automation, but it can also improve the content and impact of both assessment and intervention. Although there are many reports of VR for analgesia 30,49,56 and sedation, 54 there are few examples of attempted use in chronic pain. 34 Notable exceptions include randomized controlled trials of skills-based interventions with a focus on emotional self-regulation 4,12,24,25 and rehabilitation interventions with a focus on education and increasing movement.…”
Section: Introductionmentioning
confidence: 99%